Bacteriocin: A new strategic antibiofilm agent in food industries. (September 2021) - Kirtonia, Kohima; Salauddin, Molla; Bharadwaj, Kaushik Kumar; Pati, Siddhartha; Dey, Ankita; Shariati, Mohammad Ali; Tilak, Vijay Kumar; Kuznetsova, Elena; Sarkar, Tanmay
Abstract: Contamination of food products with microorganisms from various sources is a serious concern as it not only affects the food quality also leads to spoilage and therefore may cause several illnesses. Chemical preservatives may not be considered as a potential way as it has many disadvantages. The use of bio-preservatives can replace it. Bacteriocins are recently drawing attraction to be used in food products because of several benefits. These are antibiotics that can act against pathogenic microorganisms. It is absolutely safe to use them and can be easily digested in the human body. Bacteriocins are of three types and each one has a specific mechanism of action against biofilms. Biofilms are found in the extracellular matrix of different colonizing species and in the food industry they can be formed easily in different conditions. In specific conditions, bacteriocins cannot function against microorganisms and to enhance their functions hurdle technology is found highly suitable. It has been observed that the use of hurdle technology can promote the activity of bacteriocins to a greater extent. The incorporation of bacteriocins into packaging films can protect the food product from spoilage. There are several ways to insert bacteriocin into packaging material. This method is a great option to enhance the shelf life of food products by reducing the number of spoilage organisms. Further study is required to understand its mechanism of action more vividly which may help to use them as a bio preservative in the food industry in a broader spectrum.